EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING TERHADAP PRESTASI BELAJAR MATEMATIKA DITINJAU DARI KEAKTIFAN SISWA KELAS VII SMP N 2 TEMPURAN TAHUN AJARAN 2013/2014 - Dakusta Puspitasari; Agustina Sri Purnami (UNION: Jurnal Ilmiah Pendidikan Matematika, 2015)
This research aims to know the information about the tendency of the mathematics learning achievement and activeness of students in SMP N 2 Tempuran VII grade by snowball throwing and conventional model, to determind which method will give good achievement in mathematics, between cooperative snowball throwing type and the conventional method, to know which the mathematics learning achievement that is better among high, medium, and low activeness, to know the interactions between application of learning model and activeness level. The population of this research was all students of class VII consist of 5 classes in SMP N 2 Tempuran 2013/2014. The research sample of 2 classes was taken by cluster sampling technique. The data analysis uses descriptive analysis and two-way ANAVA analysis. The results of the analysis in the research are: 1) the mathematics learning achievement of class experiment is very high (), (2) the mathematics learning achievement of class control is high (, (3) the activeness of class experiment is moderate (), (4) The activeness of class control is low (), (5) Class experiment has better learning achievement than class control (= 4.5386), (6) the mathematics learning achievement of students who have high activeness is better than students who have moderate activeness, the mathematics learning achievement of students who have moderate activeness is better than students who have low activeness, the mathematics learning achievement of students who have high activeness is better than students who have low activeness (= 9.94245), (7) There is no interaction between learning model and activeness level of students based on the mathematics learning achievement of students. (Â = 4.555).